Bromodomain Inhibitors as Therapeutics for Herpesvirus-Related Disease: All BETs Are Off? - Groves, Ian J.; Sinclair, John H.; Wills, Mark R. (Frontiers in Cellular and Infection Microbiology, 2020)
Although the ubiquitous human herpesviruses (HHVs) are rarely associated with serious disease of the healthy host, primary infection and reactivation in immunocompromised individuals can lead to significant morbidity and, in some cases, mortality. Effective drugs are available for clinical treatment, however resistance is on the rise such that new anti-viral targets, as well as novel clinical treatment strategies, are required. A promising area of development and pre-clinical research is that of inhibitors of epigenetic modifying proteins that control both cellular functions and the viral life cycle. Here, we briefly outline the interaction of the host bromo- and extra-terminal domain (BET) proteins during different stages of the HHVs' life cycles while giving a full overview of the published work using BET bromodomain inhibitors (BRDis) during HHV infections. Furthermore, we provide evidence that small molecule inhibitors targeting the host BET proteins, and BRD4 in particular, have the potential for therapeutic intervention of HHV-associated disease.